Disruption: inside the largest counterterrorism investigation in history - Peritz, Aki (Potomac Books, an imprint of the University of Nebraska Press, 2021)
"Disruption tells the story of the conspiracy to simultaneously destroy several passenger jets over the Atlantic Ocean in 2006 and the desperate efforts by the British, Americans, and Pakistanis to crush the conspiracy before the bombs went off in the largest counterterrorism investigation in history"--